x = 5
==========
3x - 9 = -2x + 16
Balance the equation by adding 2x and 9 to both sides:
3x + 2x = 16 + 9
5x = 25
Divide both sides by 5 to get value for x:
x = 5
-5x+3(x+8)=16-2x
3x + 8 = 2x +28 3x - 2x = 28 - 8 x=20
3x+56 = 2x+4 3x-2x = 4-56 x = -52
-3x + (-18) = 2x + 7 +18 +18 -3x = 2x +25 -2x -2x -5x = 25 ----- ----- -5 -5 x=-5 *------- equals a division line
2x + 2 = 3x - 57 = x
-5x+3(x+8)=16-2x
1
(5, 1)
2x+3x = 5x
3x+5 = 2x+13 3x-2x = 13-5 x = 8
3x + 8 = 2x +28 3x - 2x = 28 - 8 x=20
3x+56 = 2x+4 3x-2x = 4-56 x = -52
-2x^4+16 +2x^4+9-3x^5=-3x^5+25. There is no "answer" because there is no equation.
3x
-3x + (-18) = 2x + 7 +18 +18 -3x = 2x +25 -2x -2x -5x = 25 ----- ----- -5 -5 x=-5 *------- equals a division line
3x - 3 = 2x + 6 3x = 2x + 9 x = 9
2x + 2 = 3x - 57 = x